Comparative efficacy and safety of teriparatide versus bisphosphonates in osteoporosis: a meta-analysis - Jin, Huan; Dong, Ying; Huang, Cai; Wang, Di; He, Ziyi; Shen, Lin; Ma, Chen; Wang, Zixian; Shi, Siwei; Shuai, Bo (Frontiers in Surgery, 2025)
ObjectivesThis meta-analysis systematically compared the efficacy and safety of teriparatide and bisphosphonates in treating osteoporosis (OP) to inform optimal treatment strategies.MethodsA comprehensive literature search was conducted in PubMed, Embase, Cochrane Library, Web of Science, and Google Scholar from inception through October 2024. Randomized controlled trials comparing teriparatide and bisphosphonates for OP were included. Primary outcomes included vertebral/non-vertebral fracture risk reduction and lumbar spine/femoral neck bone mineral density (BMD) improvements. Data were analyzed using RevMan 5.3, with dichotomous data assessed via odds ratios (OR) and continuous data via mean differences (MD), both reported with 95% confidence intervals (CI).ResultsThirteen studies involving 4,420 patients were analyzed (six Grade A, four Grade B, three Grade C). Teriparatide significantly reduced vertebral [OR = 0.40, 95% CI = (0.33, 0.49), p < 0.00001] and non-vertebral fracture risks [OR = 0.58, 95% CI = (0.54, 0.70), p < 0.00001] compared to bisphosphonates. At 12 months, teriparatide showed greater improvements in lumbar spine BMD [MD = 2.72, 95% CI = (2.44, 3.00), p < 0.00001] and femoral neck BMD [MD = 1.66, 95% CI = (0.42, 2.90), p = 0.0090]. In studies with >18-month follow-ups, teriparatide maintained superior lumbar spine BMD [MD = 4.65, 95% CI = (4.28, 5.03), p < 0.00001] and femoral neck BMD [MD = 1.42, 95% CI = (0.57, 2.26), p = 0.0010] improvements. Adverse event rates were comparable between teriparatide and bisphosphonates [MD = 1.03, 95% CI = (0.88, 1.20), p = 0.73].ConclusionTeriparatide demonstrated superior efficacy in reducing vertebral/non-vertebral fracture risks and improving BMD in both short- and long-term treatments, with a safety profile comparable to bisphosphonates.